Deskripsi Masalah Anak Tuna Rungu di SD Swasta At-Taufiq - Sinaga, Harwansyah Putra; Simanullang, Annisya Rahma; Pulungan, Alimatuk Sakdiyah; Harahap, Mutiara (Al-Hayat: Natural Sciences, Health & Environment Journal, 2023)
Interpersonal communication occurs between at least two people, including between speech-impaired children and the people around them. The problem that arises is that speech-deaf children have weaknesses in hearing and speaking, resulting in hampered interpersonal communication because not everyone understands the symbols used by speech-deaf children in communicating. The theory used in this study belongs to the theory group of interpersonal messages, namely the theory of symbolic interactionism from George Herbert Mead. Symbolic interaction is a means for deaf children to understand everything that happens around them. This theory was chosen because the research object taken was the interaction between the therapist and the speech-deaf child during interpersonal communication through the use of verbal and nonverbal symbols. This study uses a qualitative research method, namely case studies. This study aims to find out how interpersonal communication verbally and nonverbally occurs between a therapist and a child with hearing impairment in communication skills training. Research was conducted through in-depth interviews (in-depth interviews), observation, and documentation. The research sample was taken through purposive sampling by specifying special characteristics according to the research objectives. The samples taken were five out of seven speech-deaf children and five out of six therapists at the Surakarta State Extraordinary School Clinic (SLBN) with consideration of the age of the speech-deaf children and the therapists who provided therapy to them.The results of this study indicate that speech-deaf children are taught to use lip reading more than sign language. The therapist provides practice by inviting the child to feel the sound vibrations when the therapist speaks and asking the child to imitate the therapist’s words. The limitation of this research is the inability of the researcher to directly interact with the deaf children because the researcher does not yet have sufficient ability to communicate using sign language. During the research, it was found that deaf children combined lip reading with sign language in communicating with others. If balanced with consistent use of hearing aids, the ability to hear children with hearing impairments will get better. Keywords; Interpersonal Communication, Speech-deaf children, communication skills training.